Tolerance of discomfort glare from a large area source for work on a visual display - Rodriguez, Roberto Germán (2012)
A large variability in response is usually found when assessing discomfort glare by semantic differential scaling. This issue may be addressed by considering the individual's tolerance to glare, so we designed an experiment to describe the differences in glare sensation votecaused by a simulated window while glaresensitive and glare-insensitive subjects performed a computer task. The luminance and size of the window had the same statistically significant effect on glare sensation for both groups. However, when occasionally looking directly at the glare source, glare-sensitive people experienced more glare than insensitive persons with a relative risk of being disturbed that varied from 2.70 to 6.75. Our data suggest that the glare threshold should be redefined to consider glare tolerance to achieve a glare-free, inclusive visual environment.